2007
DOI: 10.1029/2005jd006109
|View full text |Cite
|
Sign up to set email alerts
|

Radiosonde humidity corrections and potential Atmospheric Infrared Sounder moisture accuracy

Abstract: [1] Although there are a number of sources of radiosonde data for validation of observations from other atmospheric sensors, routine operational sondes remain the main source for a large volume of data. In this study radiosonde moisture profiles are renormalized using Global Positioning System (GPS) Integrated Precipitable Water (IPW) vapor. The GPS-adjusted radiosonde humidity profiles are then compared to the Atmospheric Infrared Sounder (AIRS) measurements. As a check, AIRS measurements are also compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…This shows that the larger the value of an observation, the higher the probability of MLS being wetter than AIRS, consistent with the findings of Read et al [2007]. A tendency toward the mean in AIRS is noted by McMillin et al [2007] in their comparison of AIRS total precipitable water vapor with ground‐based sensors; a similar effect may be occurring for AIRS UTWV observations. However, as argued by Read et al [2007], MLS tends to overestimate scenes wetter than 400 ppmv.…”
Section: Comparison Of Matched Observationssupporting
confidence: 90%
“…This shows that the larger the value of an observation, the higher the probability of MLS being wetter than AIRS, consistent with the findings of Read et al [2007]. A tendency toward the mean in AIRS is noted by McMillin et al [2007] in their comparison of AIRS total precipitable water vapor with ground‐based sensors; a similar effect may be occurring for AIRS UTWV observations. However, as argued by Read et al [2007], MLS tends to overestimate scenes wetter than 400 ppmv.…”
Section: Comparison Of Matched Observationssupporting
confidence: 90%
“…According to the results of previous studies, the AIRS TPW data showed that they are wetter at low altitudes (800 hPa) and drier at higher altitudes (300~600 hPa) when compared with the results of numerical models (Pierce et al 2006), and the accuracy was about 15% within the altitude rage of 2 km from the ground surface (Divakarla et al 2006). However, since the accuracy verification results from the previous studies are focused on the tropical region (Pierce et al 2006) or Europe and the USA (Fetzer et al 2003, McMillin et al 2007, there have been no sufficient verification researches conducted specifically for the observation environment in Korea.…”
Section: Data Collection and Analytical Methodsmentioning
confidence: 77%
“…There are a number of previous studies on the accuracy verification of AIRS TPW data using radiosondes and numerical models (Fetzer et al 2003, Divakarla et al 2006, Pierce et al 2006, McMillin et al 2007). According to the results of previous studies, the AIRS TPW data showed that they are wetter at low altitudes (800 hPa) and drier at higher altitudes (300~600 hPa) when compared with the results of numerical models (Pierce et al 2006), and the accuracy was about 15% within the altitude rage of 2 km from the ground surface (Divakarla et al 2006).…”
Section: Data Collection and Analytical Methodsmentioning
confidence: 99%
“…It takes about 40 minutes to reach 16 km of altitude in this elevation speed and about 90 minute to reach 30 km of altitude (World Meterorological Organization 2008). Thus, after 30 minutes following the flying, the radiosonde reaches about 12 km of altitude where most of the water vapor in the atmosphere is contained (McMillin et al 2007).…”
Section: Characteristics Of the Data And The Methods Of The Studymentioning
confidence: 99%